Total Sitting Time and Sitting Pattern in Postmenopausal Women Differ by Hispanic Ethnicity and are Associated With Cardiometabolic Risk Biomarkers. Issue 4 (18th February 2020) - Chang, Ya‐Ju; Bellettiere, John; Godbole, Suneeta; Keshavarz, Samaneh; Maestas, Joseph P.; Unkart, Jonathan T.; Ervin, Daniel; Allison, Matthew A.; Rock, Cheryl L.; Patterson, Ruth E.; Jankowska, Marta M.; Kerr, Jacqueline; et al.
Abstract : Background: Sedentary behavior is pervasive, especially in older adults, and is associated with cardiometabolic disease and mortality. Relationships between cardiometabolic biomarkers and sitting time are unexplored in older women, as are possible ethnic differences. Methods and Results: Ethnic differences in sitting behavior and associations with cardiometabolic risk were explored in overweight/obese postmenopausal women (n=518; mean±SD age 63±6 years; mean body mass index 31.4±4.8 kg/m 2 ). Accelerometer data were processed using validated machine‐learned algorithms to measure total daily sitting time and mean sitting bout duration (an indicator of sitting behavior pattern). Multivariable linear regression was used to compare sitting among Hispanic women (n=102) and non‐Hispanic women (n=416) and tested associations with cardiometabolic risk biomarkers. Hispanic women sat, on average, 50.3 minutes less/day than non‐Hispanic women ( P <0.001) and had shorter (3.6 minutes less, P =0.02) mean sitting bout duration. Among all women, longer total sitting time was deleteriously associated with fasting insulin and triglyceride concentrations, insulin resistance, body mass index and waist circumference; longer mean sitting bout duration was deleteriously associated with fasting glucose and insulin concentrations, insulin resistance, body mass index and waist circumference. Exploratory interaction analysis showed that the association between mean sitting bout duration and fasting glucose concentration was significantly stronger among Hispanic women than non‐Hispanic women ( P ‐interaction=0.03). Conclusions: Ethnic differences in 2 objectively measured parameters of sitting behavior, as well as detrimental associations between parameters and cardiometabolic biomarkers were observed in overweight/obese older women. The detrimental association between mean sitting bout duration and fasting glucose may be greater in Hispanic women than in non‐Hispanic women. Corroboration in larger studies is warranted.